2018
DOI: 10.1007/s10880-018-9573-8
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Seeking Psychological Help: An Integrative Model Based on Contact, Essentialist Beliefs About Mental Illness, and Stigma

Abstract: Based on intergroup contact theory, a proposed comprehensive model of attitudes towards seeking professional psychological help was tested, including both potential barriers to mental health help-seeking (i.e., public stigma and self-stigma of seeking help, prejudicial and essentialist beliefs about mental illness, intergroup anxiety) and potential facilitators (i.e., direct and extended contact with persons with mental illness). Relevant measures were completed by 119 community-dwelling participants. Path ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Alternatively, it may be that the direct contact with a person with lived experience of mental illness, which was part of the intervention, helped alleviate participants' stigma toward mental illness, and in turn reduced student's stigma toward seeking psychological help. This is supported by Hantzi et al's study (34) which found that when there are lesser negative beliefs about mental illness, the self-stigma for seeking psychological help is reduced, while positive help-seeking attitudes are increased (34).…”
Section: Recognition Of Depressionmentioning
confidence: 78%
“…Alternatively, it may be that the direct contact with a person with lived experience of mental illness, which was part of the intervention, helped alleviate participants' stigma toward mental illness, and in turn reduced student's stigma toward seeking psychological help. This is supported by Hantzi et al's study (34) which found that when there are lesser negative beliefs about mental illness, the self-stigma for seeking psychological help is reduced, while positive help-seeking attitudes are increased (34).…”
Section: Recognition Of Depressionmentioning
confidence: 78%
“…Based on the theory of planned behavior (TPB) (20), attitude can indirectly influence help-seeking behavior via intention (21), and it is a precursor to help-seeking intention and actual help behaviors (22). Thus, improving help-seeking attitude is the first step in promoting further help-seeking behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of Medical Expenditures Panel Survey data on primary care and special mental health visits showed racial and ethnic disparities in mental care visits, suggesting that Latinx adults have lower access to mental health services compared with their same-age white counterparts ( Jones et al, 2018 ). Taken together, these experiences and perceptions may lead to older Latinx adults’ greater stigmatization and negative attitudes toward treatment of “less severe” pathologies such as depression or anxiety ( Hantzi et al., 2019 ) and lower utilization of mental health services for these issues ( Villatoro et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%